The Effect of Early Marriages on Social Development in Kakabara Town Council, Kyegegwa District. - Birungi, Beatrice (Kabale University, 2023)
The study research report focused on the findings of the effect of early marriage on socio-economic development. The objectives of the study to find out the factors leading to early marriage on social development in Kakabara Town council Kyegerwa district, to find out the effect of early marriage on social development in Kakabara Town council Kyegerwa district, to find out the measures to curb early marriage on social development in Kakabara Town council Kyegerwa district. In chapter two, there was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on early marriage as an independent variable and socio-economic development as the dependent variable. In chapter three this is where the methods of data collection were put into action. The research used both qualitative and quantitative methods of data collection and analysis. A sample of 40 respondents was used in the study and both simple random sampling techniques and purposive sampling in collecting and analyzing data were used to provide equal chances to the sample size. In chapter four showed the findings of the study obtained from the field interpreting the results and analyzing basing on the specific objectives of the study and Chapter five portrayed the summary of findings, findings of the study revealed that female respondents were highly involved in the study. The study recommended that there should be provision of sanitary materials; should be provided by the government and parents to girls. These materials include; pads and other materials used. This will encourage many girls to study instead of them involved in worthless activities such as early marriage and there should be continued offering of Counseling and Guidance services; this should be done by parents and school administrators on the advantages or importance of good morals among girl child students in the community. This will change the behaviors of students positively and lead to better behaviors in the community and the society as a whole. This is because some parents were not participating in teaching their children about life style situations. The study concluded that there were socioeconomic factors affecting early marriage in Kakabara town council as including Low income presented, Child labor, Parental literacy, Parental concern, Poverty, Level of income, and Family size. The findings of the study conclude that there were problems brought about by socio economic factors affecting early like; Lack of savings, poverty, School fees, competition, Living conditions, Change in health conditions, and Welfare status.